Determinants in health and lifestyle style of schools: longitudinal study (Research, Society and Development, 2020)
Aiming to analyze the contributions of interventions in the school environment, aiming at health promotion, health determinants and lifestyle in schoolchildren. For evaluation, eight tests were carried out between 2011 and 2014, always at the beginning and end of each school year. Anthropometric measures were applied and lifestyle questionnaires were applied to students in grades 6 through 9 of elementary school. We considered the students who participated in 4 tests, and performed a descriptive and inferential statistical analysis, for the association was used the chi-square test. The results of physical activity showed that most of the students did not practice the recommended one. In nutritional knowledge many students had low knowledge and regular eating habits. In nutritional status, most students were eutrophic. In body image many students were dissatisfied. It was concluded that the results pointed to behavioral changes in the health determinants of the investigated patients.